Optimization of pin-fin heat sinks using anisotropic local thermal nonequilibrium porous model in a jet impinging channel - Kim, SY; Kuznetsov, AV (TAYLOR & FRANCIS INC, 2003)
A numerical study has been carried out to optimize the thermal performance of a pin-fin heat sink. A pin-fin heat sink, which is placed horizontally in a channel, is modeled as a hydraulically and thermally anisotrapic porous medium. A uniform heat flux is prescribed at the bottom of the heat sink. Cool air is supplied from the top opening of the channel and exhausts to the channel outlet. Comprehensive numerical solutions are derived from the governing Navier-Stokes and energy equations using the Brinkman-Forchheimer extended Darcy model and the local thermal nonequilibrium (LTNE) porous model for the region occupied by the heat sink. Results from this study indicate that the anisotropy in permeability and solid-phase effective thermal conductivity changes substantially with the variation of porosity. Optimum porosity for maximum heat dissipation depends on the pin-fin thickness, the pin-fin height, and the Reynolds number. A correlation for predicting the optimum porosity for a pin-fin heat sink is proposed. Generally, in the case of thin pin-fins the heat sink should be designed to have a high porosity, while in the case of thick pin-fins the heat sink should be designed to have a relatively low porosity.
Keywords: BOUNDARY-CONDITIONS; FLUID; FLOW; PERFORMANCE; DISPERSION